2016
DOI: 10.1038/srep39520
|View full text |Cite
|
Sign up to set email alerts
|

Chronic hepatitis C infection–induced liver fibrogenesis is associated with M2 macrophage activation

Abstract: The immuno-pathogenic mechanisms of chronic hepatitis C virus (HCV) infection remain to be elucidated and pose a major hurdle in treating or preventing chronic HCV-induced advanced liver diseases such as cirrhosis. Macrophages are a major component of the inflammatory milieu in chronic HCV–induced liver disease, and are generally derived from circulating inflammatory monocytes; however very little is known about their role in liver diseases. To investigate the activation and role of macrophages in chronic HCV–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
47
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 32 publications
5
47
0
1
Order By: Relevance
“…Three main macrophage clusters that were significantly increased in the patients with advanced fibrosis included CD68+ macrophages, CD68+Mac387+ monocyte-derived macrophages, and CD163+CD16+ antiinflammatory macrophages (Fig 4D, #3,#4,#5). The results of these imaging analyses confirm previous observations that suggest a predominance of CD14+ cells during homeostasis and increased accumulation of CD16+CD163+ macrophages in human liver diseases (3,6,11,13). The overall decrease in CD14 in patients with advanced fibrosis when compared to controls is likely due to lower expression of CD14 not only on macrophages, but also on liver sinusoidal endothelial cells, which are also known to express this antigen and have been shown to decrease expression upon activation, such as that that occurs with HCV infection (29).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Three main macrophage clusters that were significantly increased in the patients with advanced fibrosis included CD68+ macrophages, CD68+Mac387+ monocyte-derived macrophages, and CD163+CD16+ antiinflammatory macrophages (Fig 4D, #3,#4,#5). The results of these imaging analyses confirm previous observations that suggest a predominance of CD14+ cells during homeostasis and increased accumulation of CD16+CD163+ macrophages in human liver diseases (3,6,11,13). The overall decrease in CD14 in patients with advanced fibrosis when compared to controls is likely due to lower expression of CD14 not only on macrophages, but also on liver sinusoidal endothelial cells, which are also known to express this antigen and have been shown to decrease expression upon activation, such as that that occurs with HCV infection (29).…”
Section: Discussionsupporting
confidence: 88%
“…Interpretation of CD163+ macrophage function has varied depending on the study; some reports support a tolerogenic phenotype with high basal expression in non-diseased liver, while other studies suggest they confer a characteristic "M2" phenotype that is increased in portal tracts and lobules of patients with chronic HCV (11,13,32). This study reveals a more nuanced result where several macrophage subtypes expressing this antigen are present in liver biopsies from control patients; however, the number of CD163+ macrophage phenotypes increased concomitant with disease state (Fig 7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro experiment, using IL-4 induced M2 polarization, we found myricetin induced M2-polarized macrophage genes (Ym-1, Arg1, CD163, and IL-10) similarly IL-4-induced macrophages (Figure 6F). Noticeably, several previous studies have also demonstrated that M2 macrophages activation (Ym-1 + , CD206 + , or CD163 + ) was induced and had the potential effect on inflammatory response and fibrogenesis both in chronic liver diseases and in animal models (47,(50)(51)(52). However, it's worth to note that M2 macrophages significantly decreased at the later stage of NASH and fibrosis (51).…”
Section: Discussionmentioning
confidence: 89%
“…M2 macrophages are activated by Th2 cytokines, such as IL-13 and IL-4, which are abundant in chronic infectious. Excessive M2 activation contributes to chronic liver fibrosis by secreting pro-fibrotic cytokines (45, 60). In our cellular model, the M2 macrophage pathway was activated by IL-4/IL-13 cytokines.…”
Section: Discussionmentioning
confidence: 99%